Erik Møller: Grundtvig som samtidshistoriker - Michelsen, William (Grundtvig-studier, 1951)
Erik Møller: Grundtv ig som Samtidshistoriker. (Grun d tv ig as a Historian of Contemporary Events). Copenhagen (Gy ld end a l) , 1950. 203 pages. Re viewed b y William Michelsen. In this book the author has aimed at throwing a new light over the personality of Grundtvig in order to awaken an understanding of his thoughts among circles formerly alien to them. Being a historian of contemporary events himself he has chosen to consider Grundtvig from the same point of view. But was Grundtvig a historian of contemporary events at all, or to what extent is it reasonable to regard him as such? Among his historical writings only the first short “ World’s Chronicle” (1812) includes contemporary history, which is considered exclusively from a moral and religious point of view. Not even in the series of lectures on contemporary history delivered in 1838 (first published after his death under the title “ Mands Minde” ) does he aim at giving any scholarly, objective presentation of the facts, only at recording the impressions which the events of the period made on him personally. Erik Møller’s criticism therefore both of these and Grundtvigs other numerous comments on contemporary affairs must often appear unfair or subjective. The author encomprises his opinion in the words, “ that Grundtvig was really not a man of visions, but a man of facts.” In relation to this it must be held that Grundtvig was a man both of visions and of facts. His view of history — including contemporary — cannot possibly be understood unless it is set in the context of his “ visions” . His greatness is measured mainly by his power to see and understand the crisis of culture which is now in its acute stage, but which began with the French Revolution when Grundtvig was a boy. Whether or not one agrees with Grundtvig in his interpretation of this crisis of culture, it is at this point that any discussion of his thought must begin. In spite of these and some minor critical remarks however it must be noticed, that Erik Møller’s investigation is very well documented, and that especially his criticism of the common aspect of Grundtvig as a “ prophet” is of great value.